A Case Presentation: Decidualized Endometrioma Mimicking Ovarian Cancer during Pregnancy - Aybike Tazegül; Özlem Seçilmiş Kerimoğlu; Feyza Nur İncesu; Nasuh Utku Doğan; Setenay Arzu Yılmaz; Çetin Çelik (Hindawi Limited, 2013)
During pregnancy, masses that are larger than 5 cm and appearing in the Doppler ultrasonography as having increased blood flow, echoes of heterogeneous density, and containing solid components are suspicious for malignancy; however, differential diagnosis of decidualized endometriomas should also be considered. The patient was an 8 weeks pregnant primigravida. The ultrasonographic evaluation showed a cystic mass of size 65 × 57 mm in the left ovary that was well circumscribed, heterogeneous, with highly dense internal echo, and containing a solid component of size 8 × 14 mm. In the 12th week, the ultrasonographic examination revealed an increase in the size of the mass and increased arterial blood flow in the mass. The patient underwent surgery. It was observed that both ovaries were adherent in the Douglas pouch and that the left ovary contained an endometrioma of size 8cm. While the capsule was being peeled, lesions of soft density, with irregular surfaces, and with adhesion in the Douglas pouch were observed. The results of the frozen section revealed decidualized endometrioma and decidual structures. Even in pregnant women when adnexal masses are encountered and the ultrasonography, Doppler, MRI, and CA 125 level analysis still do not favor endometriosis, decidualized endometrioma should be considered in the differential diagnosis.